Analysis Of The Influence Of Financial Literacy And Digital Literacy Of The Community On Smart Branch Mandiri - Nahda Alyani Sharfina; Cepi Pahlevi; Fauzi R. Rahim (International Journal of Business and Quality Research, 2023)
As technology evolves, digital banking is beginning to penetrate every corner of life on the financial, consumer and even customer experience sides. In response to the transition of industry growth towards this digital era, a number of activities have begun to adapt to the current conditions. Technological advancements that make life easier have also penetrated the financial sector. Smart Branch is designed to accommodate customer needs based on the level of digital adoption by presenting a service process that is integrated with digital channels and self-service machines. The purpose of this study was to examine the effect of financial literacy and digital literacy on Bank Mandiri's smart Branch in using digital banks The digital transformation step is a push to increase digital financial literacy in Indonesia. The type of research in this study is descriptive research using a quantitative approach with primary data type